2023
DOI: 10.3390/md21030159
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Pepsin- and Acid-Soluble Collagen from the Swim Bladders of Megalonibea fusca

Abstract: There is a growing demand for the identification of alternative sources of collagen not derived from land-dwelling animals. The present study explored the use of pepsin- and acid-based extraction protocols to isolate collagen from the swim bladders of Megalonibea fusca. After extraction, these acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) samples respectively were subjected to spectral analyses and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) characterization, revealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
(69 reference statements)
3
5
0
Order By: Relevance
“…G and G increased with increasing pH in the sweep frequency range of 0.01-10 Hz, indicating that pH can improve the viscoelasticity of the collagen solution. Moreover, when the pH (8,10) was greater than pI, G was higher than G in the scanning frequency range of 0.01-10 Hz. This suggests that elasticity is preferred to viscosity and that elastic behaviour is dominant in solution systems, with solutions exhibiting solid-like behaviour.…”
Section: Rheological Propertiesmentioning
confidence: 85%
See 3 more Smart Citations
“…G and G increased with increasing pH in the sweep frequency range of 0.01-10 Hz, indicating that pH can improve the viscoelasticity of the collagen solution. Moreover, when the pH (8,10) was greater than pI, G was higher than G in the scanning frequency range of 0.01-10 Hz. This suggests that elasticity is preferred to viscosity and that elastic behaviour is dominant in solution systems, with solutions exhibiting solid-like behaviour.…”
Section: Rheological Propertiesmentioning
confidence: 85%
“…This could be because pH led to a change in internal interactions of the collagen, which changed the collagen structure. Previous literature reported that the fibrous and sheet membrane structure of collagen facilitates cell growth, wound healing and new tissue formation [8]. Therefore, it could be used in practical biomedical applications, such as wound management, biofilms and drug delivery by modifying the morphology upon adjusting the pH.…”
Section: Morphology Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fresh sea eels were purchased from Zhoushan Farmers' Vegetable Market and pretreated before being stored at −20 The extraction of fish bladder collagen was performed following the method described by Mo et al [33]. The extraction process involved a series of sequential steps.…”
Section: Methodsmentioning
confidence: 99%